2020
DOI: 10.1037/spq0000406
|View full text |Cite
|
Sign up to set email alerts
|

Promoting resilience: A preschool intervention enhances the adolescent adjustment of children exposed to early adversity.

Abstract: Two hundred ninety-four children from low-income families (58% White, 17% Latinx, 25% Black; 54% girls; M age ϭ 4.49 years old at study entry) were recruited from Head Start classrooms to participate in a randomized-controlled trial of the project Research-based, Developmentally Informed (REDI) preschool intervention and then followed longitudinally for 10 years through 9th grade. At study entry, parents reported on their children's exposure to adverse childhood experiences (ACEs). Youth reported on their feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Children who have experienced adversity need adults who can assist in improving their physical health and mental well-being, while parents and educators need to play a key role in recognizing and reacting to children experiencing early trauma by creating environments that reduce short-term effects and can promote the growth of protective factors (Sciaraffa et al, 2018). In a 10-year longitudinal study conducted by Sanders et al (2020), children with high levels of ACE exposure who participated in the Research-based, Developmentally Informed (REDI) preschool intervention demonstrated decreased social-emotional distress and stronger school bonding experiences in adolescence. REDI is a resilience-focused, school-based intervention that has the potential to be delivered in classrooms to many young, at-risk children at a relatively low cost (Sanders et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who have experienced adversity need adults who can assist in improving their physical health and mental well-being, while parents and educators need to play a key role in recognizing and reacting to children experiencing early trauma by creating environments that reduce short-term effects and can promote the growth of protective factors (Sciaraffa et al, 2018). In a 10-year longitudinal study conducted by Sanders et al (2020), children with high levels of ACE exposure who participated in the Research-based, Developmentally Informed (REDI) preschool intervention demonstrated decreased social-emotional distress and stronger school bonding experiences in adolescence. REDI is a resilience-focused, school-based intervention that has the potential to be delivered in classrooms to many young, at-risk children at a relatively low cost (Sanders et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a 10-year longitudinal study conducted by Sanders et al (2020), children with high levels of ACE exposure who participated in the Research-based, Developmentally Informed (REDI) preschool intervention demonstrated decreased social-emotional distress and stronger school bonding experiences in adolescence. REDI is a resilience-focused, school-based intervention that has the potential to be delivered in classrooms to many young, at-risk children at a relatively low cost (Sanders et al, 2020). Furthermore, it provides evidence that increasing protective factors and resiliency in childhood promotes stronger mental health outcomes later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that SEL programs have successfully promoted protective factors for students exposed to ACEs [23,24]. Using data from the Chicago Longitudinal Study, Niles and colleagues [24] found that adolescents who had been exposed to potential adversities during preschool benefitted from an SEL program.…”
Section: Aces and Selmentioning
confidence: 99%
“…Indeed, there is a growing and clear weight of evidence that the promotion of SECs, for example emotion regulation (e.g., inhibitory control) and cognitive ability (e.g., working memory) are associated with several benefits (e.g., Moltrecht et al, 2020;Sanders et al, 2020). Longitudinal and intervention studies support a prospective association between SEC and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…A follow up of the REDI cohort, by Bierman et al (2020), 8-10 years post-intervention (children aged 12-13 and 14-15, respectively) indicated enduring benefits for intervention children, relative to control children in reduced conduct and emotional problems, as well as fewer intervention children evidencing clinically significant problems, namely fewer problems with peers, emotions, and conduct as measured by the Strengths and Difficulties Questionnaire (SDQ). Taken together, the U.S. evidence base on preschool PATHS indicates the intervention has shown an ability to not only protect children in the general population (i.e., universal prevention) but can also be beneficial in protecting higher risk groups of children, for example children exposed to poverty and/or adverse childhood experiences (e.g., better than expected reductions in socialemotional distress and increased school bonding see Gamze et al, 2019;Sanders et al, 2020). Thus, the evidence base for preschool PATHS in the U.S. is generally positive and bodes well for international replication.…”
Section: Introductionmentioning
confidence: 99%